Against Negation: Suicide, Self-Consciousness, and Jibanananda Das's Poem, "One Day Eight Years Ago". (22nd June 2015) - Ray, Manas
Abstract: Jibanananda Das (1899–1954) is widely revered as the preeminent poet of post-Tagore Bengali literature. His oeuvre is unremittingly autobiographical, narrating desultory journeys into a vulnerable yet stoic, companionless life. The poem that the paper analyses is one of his most well known. Two streaks of narrative run parallel in the poem: the protagonist's act of suicide without any apparent reason and the ceaseless brutality of nature as a way of life. The poem has occasioned a large body of critical literature. As against the prevalent interpretation of the poem, which privileges self-consciousness and a dialectical scheme of interpretation, we set off a Foucauldian, archeo-genealogical reading. In our reading, the poem is a theater of many voices constituting a matrix of language, which, strictly speaking, is a nonlanguage—articulations that perfectly fold back against one another to implicate in a tautological bind the originary meaninglessness of living and of life's constitutive cruelty. Here negation is uncontainable and illimitable, always spilling over, always open to possibilities of being otherwise, its trail running in negating—almost inevitably—negation itself and thus gesturing an aleatory renewal of a space for the political.